2020
DOI: 10.1111/acps.13199
|View full text |Cite
|
Sign up to set email alerts
|

Potential language bias in systematic reviews on the use of coercion in psychiatry

Abstract: Gooding et al. (1) present an international scoping review on studies that examined measures to reduce coercion in mental health services. The topic is of high interest, and they conducted a wide search in a reasonable set of databases, yielding eventually 121 empirical research papers. 65 out of these papers, more than the half, stem from countries where English is spoken as native or official language (the latter applies to countries such as India or Ghana). In contrast, none stems from a French-speaking cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is possible that the publication pattern represented by the core group of countries driving the major trends in this review is related to both the climatic scope of our approach and the inability of the research team to translate publications in languages other than English. Systematic issues such as these are recognised more broadly and have the potential to result in erroneous conclusions (Moher et al 2015;Steinert 2020;Stern & Kleijnen 2020). Without extensive collaboration from researchers fluent in different languages, there is likely to be difficulties in reviewing articles published in other languages.…”
Section: Limitationsmentioning
confidence: 99%
“…It is possible that the publication pattern represented by the core group of countries driving the major trends in this review is related to both the climatic scope of our approach and the inability of the research team to translate publications in languages other than English. Systematic issues such as these are recognised more broadly and have the potential to result in erroneous conclusions (Moher et al 2015;Steinert 2020;Stern & Kleijnen 2020). Without extensive collaboration from researchers fluent in different languages, there is likely to be difficulties in reviewing articles published in other languages.…”
Section: Limitationsmentioning
confidence: 99%
“…To the best of our knowledge, in addition to the study by Ketelsen et al [16], only a very limited number of relevant papers comprising at least total hospital populations have been published, and all others only in the German language. This dearth of literature causes some problems for systematic reviews [17]. A first study published thirty years ago reported low rates of 1.9% of patients with violent acts in four hospitals in Baden-Wuerttemberg [18].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest Tilman Steinert's recent letter to the editor (1) highlighting the potential language bias in the international scoping review on the use of coercion in psychiatry, previously published by Gooding et al (2). As underlined by Professor Steinert, excluding all papers in languages other than English suggests that there is a relative paucity of research on this topic in most non‐English countries.…”
mentioning
confidence: 99%